2017
DOI: 10.1007/s11695-017-2734-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Following Bariatric Surgery: Our 31-Year Experience

Abstract: Purpose Identify the cumulative incidence of post-bariatric surgery hypoglycemia (PBSH), describe its symptomatology, and characterize treatment patterns at a large academic institution. Materials and Methods All patients who underwent bariatric surgery at a single institution from 1985–2015 were identified using a clinical database, administrative billing data identified patients who were treated for hypoglycemia, and chart reviews were performed to make a diagnosis of PBSH based on Whipple’s triad. PBSH ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
2
13
0
3
Order By: Relevance
“…A low‐carbohydrate, low‐glycemic index diet with adequate protein and inclusion of heart‐healthy fats along with restricting alcohol and caffeine intake recently has been shown to be an effective strategy to manage hypoglycemia after bariatric surgery . In fact, most patients with hypoglycemia after bariatric surgery will respond to dietary modification or pharmacologic intervention . As an example, continuous glucose monitoring was useful in a pregnant patient with dumping syndrome after RYGB and poor adherence with conventional glucose monitoring .…”
Section: Executive Summarymentioning
confidence: 99%
“…A low‐carbohydrate, low‐glycemic index diet with adequate protein and inclusion of heart‐healthy fats along with restricting alcohol and caffeine intake recently has been shown to be an effective strategy to manage hypoglycemia after bariatric surgery . In fact, most patients with hypoglycemia after bariatric surgery will respond to dietary modification or pharmacologic intervention . As an example, continuous glucose monitoring was useful in a pregnant patient with dumping syndrome after RYGB and poor adherence with conventional glucose monitoring .…”
Section: Executive Summarymentioning
confidence: 99%
“…The natural history of post-RYGB remains uncertain. One series that identified hypoglycemia based on clinical and billing data (80) found that the median time from surgery to the hypoglycemic event was 41 months; 79% of cases identified eventually resolved. In our experience, dumping syndrome-related symptoms generally improve over time by avoiding triggers, whereas severe hypoglycemia does not.…”
Section: Prevalence Natural History and Risk Factorsmentioning
confidence: 99%
“…18 Mais de 95% dos relatos de hipoglicemia pós-cirurgia bariátrica ocorre em doentes submetidos a bypass gástrico e apenas uma minoria (2%) ocorre após sleeve gástrico. 19 Excecionalmente, já foi descrito após colocação de banda gástrica. Também ocorre em doentes submetidos a switch duodenal porém, esta técnica cirúrgica não é atualmente a preferencial no tratamento da obesidade.…”
Section: Apresentação Clínicaunclassified
“…23,46,48,49 Esta é uma solução temporária, por vezes utilizada antes de uma cirurgia mais agressiva. 19 2. Restrição da bolsa gástrica com anel ou banda ajustável.…”
Section: Terapêutica Cirúrgicaunclassified